Do Teachers Fond of Reading? Teachers’ Affective States in EFL Reading - Delti Yulita; Hesni Neno (Journal of English Language Studies, 2021)
This article presents findings from a study investigating the affective states of English teachers in East Nusa Tenggara regarding their EFL reading. Affective states related to motivation, feelings, volition, attribution and self-efficacy in EFL reading that make the readers be persistent to achieve their reading comprehension. This study used qualitative approach and the data were collected through questionnaire, interview, and observation. The participants were four English teachers in senior high school that have teaching experiences more than 10 years. The result showed that teachers’ affective states in EFL reading were high and triggered by external motivation. Regarding the feelings in EFL reading, the teachers have more positive feelings depending on text difficulties. Furthermore, the teachers showed high volition, attribution and self-efficacy in EFL reading because of internet era that allow them to access many reading sources and exercises. The analysis revealed that the teachers were more confident in this present time compared to their past experiences in EFL reading. The higher affective states could be beneficial for the teachers to overcome their reading problem and to train the teachers’ responsibility toward their own reading experience.